N′-(2,5-Dihydroxybenzylidene)-2-hydroxy-3-methylbenzohydrazide - You-Yue Han; Yong-Hong Li; Qiu-Rong Zhao (Acta Crystallographica Section E, 2010)
In the title compound, C15H14N2O4, the dihedral angle between the two benzene rings is 4.1 (2)°. The molecule adopts an E configuration with respect to the C=N bond. There are intramolecular O—H...N and O—H...O hydrogen bonds in the molecule. In the crystal structure, molecules are linked through intermolecular N—H...O and O—H...O hydrogen bonds, forming chains running along the c axis.